Proline Isomerization as a Key Determinant for Hsp90-Toxin Interactions - Kellner, Alisha; Cherubin, Patrick; Harper, James K.; Teter, Ken (Frontiers in Cellular and Infection Microbiology, 2021)
The A chains of ADP-ribosylating toxins exploit Hsp90 for translocation into the host cytosol. Here, we hypothesize that cis proline residues play a key role in toxin recognition by Hsp90. Our model is largely derived from studies on the unusual interplay between Hsp90 and the catalytic A1 subunit of cholera toxin (CTA1), including the recent identification of an RPPDEI-like binding motif for Hsp90 in CTA1 and several other bacterial toxins. Cis/trans proline isomerization is known to influence protein-protein interactions and protein structure/function, but it has not yet been proposed to affect Hsp90-toxin interactions. Our model thus provides a new framework to understand the molecular basis for Hsp90 chaperone function and Hsp90-driven toxin translocation.